Problematika guru dalam pengelolaan pembelajaran Sejarah daring (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
This research was motivated by findings at the research location, namely SMA Negeri 3 Cirebon which showed that in the process of managing online history learning, teachers found many new problems that were not previously found during the process of managing online history learning. Therefore, this study examines the problems of teachers in managing history learning with the formulation of the main problem “what problems are faced by history teachers in the management of history learning?” This study uses a descriptive study that aims to obtain a description of the management of courageous and problematic history learning found in the management of courage history learning at SMA Negeri 3 Cirebon. it also describes the efforts to overcome the problems found and the responses of students, including the learning of history at SMA Negeri 3 Cirebon. The results of the study show that there are various kinds of problems faced by teachers in all processes in learning management, starting from planning, implementing learning, to evaluating bold history learning. There are several problems that are common problems for history teachers at SMA Negeri 3 Cirebon, including problems in maintaining class and problems in carrying out historical evaluations of courage, especially in terms of skills and attitudes. All the problems that arise in the management of this courageous history learning are enough to hinder the learning process so that history learning cannot run optimally
Keywords: Learning problems; Learning management; History learning; Online learning